Restoring Sleep Health in the Post-COVID Elderly with Comorbidities: Impact of Jacobson’s Relaxation Technique in Urban Puducherry - bon. S, Sivasankari; S, Rajalakshmi (Journal of Neonatal Surgery, 2025)
Background: Sleep disturbances are a common concern among the elderly, particularly those with comorbid conditions, and have been exacerbated in the post-COVID era. Restoring sleep health in this vulnerable population is essential for enhancing overall well-being and preventing further health deterioration. Aim: This study aimed to evaluate the effectiveness of Jacobson’s Progressive Muscle Relaxation (JPMR) technique in improving sleep quality among elderly individuals with comorbidities residing in selected urban areas of Puducherry. Methodology: A quasi-experimental one-group pre-test and post-test design was adopted with 100 elderly participants aged 60 years and above, selected through random sampling. The Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality before and after the intervention. JPMR sessions were administered daily for two weeks. Data were analyzed using descriptive and inferential statistics, including paired t-tests and chi-square tests. Results: The mean PSQI score significantly decreased from pre-test to post-test, indicating improved sleep quality (p < 0.001). Significant associations were found between sleep quality and variables such as age, comorbid illness, and marital state (p < 0.05). Conclusion: The study highlights the efficacy of JPMR as a non-pharmacological intervention for improving sleep in elderly individuals with comorbidities. Holistic strategies incorporating relaxation techniques can substantially enhance sleep health in aging populations